Robert Frank, "Trolley-New Orleans" - Gallun, Lucy (The Museum of Modern Art, 2021)
During an extended road trip across the United States, Robert Frank (1924-2019) pointed his camera lens at a passing trolley in New Orleans, took a single exposure and then turned back to bustling Canal Street, where crowds of people swarmed the sidewalks. That single click of the shutter produced a picture with enduring clarity: a row of windows framing the streetcar's passengers: white passengers in the front, Black passengers in the back. Frank captured individual faces gazing from each rectangular frame, from the weary Black man in his work shirt to the young white girl just in front of him, her hand resting on the wooden sign that designated areas segregated by race. In 1958, he wrote: "With these photographs, I have attempted to show a cross-section of the American population. My effort was to express it simply and without confusion." By the time "The Americans" was published in the United States in 1959, with this image now appearing on its front cover, New Orleans streetcars and buses had been desegregated through a 1958 court order. But Jim Crow was still in full swing, the 1960s Civil Rights struggles still ahead. An essay by MoMA curator Lucy Gallun conveys how this image reverberates in new contexts today
Includes images of several photographs by Robert Frank, plus pictures by other photographers, and a Jacob Lawrence painting
Keywords: Frank, Robert -- 1924-2019; Frank, Robert / 1924-2019 / Trolley, New Orleans; Museum of Modern Art (New York, N.Y.); Photography, Artistic; Race in art; Photography / Social aspects; Segregation / United States / Pictorial works